2008
DOI: 10.1007/s11743-008-1102-6
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Aqueous Rhamnolipids Solutions Produced by Pseudomonas aeruginosa LBI

Abstract: The wetting behavior of rhamnolipids produced by Pseudomonas aeruginosa LBI strain grown on waste oil substrate and sodium dodecyl sulfate (SDS) on glass, polyethylene terephthalate (PET), poly(vinyl chloride) (PVC), poly(e-caprolactone) (PCL) and polymer blend (PVC-PCL) was investigated by the measuring contact angle of sessile drops, to determine the wetting characteristics of rhamnolipids. The comparison of the wetting profiles showed that at low SDS and rhamnolipid concentrations, the contact angle increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The comparison of the wetting profiles showed dynamic changes in the contact angle at low SDS and RL concentrations -the contact angle increased and when the concentration of the surfactant increased further, the contact angle decreased. 59 The results showed that RLs produced by P. aeruginosa LBI exhibited superior wetting abilities compared to SDS. This is the first work that evaluated the wetting properties of RLs on polymer blends.…”
Section: Formulation Of Cleaners and Wetting Agentsmentioning
confidence: 94%
See 4 more Smart Citations
“…The comparison of the wetting profiles showed dynamic changes in the contact angle at low SDS and RL concentrations -the contact angle increased and when the concentration of the surfactant increased further, the contact angle decreased. 59 The results showed that RLs produced by P. aeruginosa LBI exhibited superior wetting abilities compared to SDS. This is the first work that evaluated the wetting properties of RLs on polymer blends.…”
Section: Formulation Of Cleaners and Wetting Agentsmentioning
confidence: 94%
“…59 Determination of the HLB value, which varies between 0 and 20, enables the prediction of the behavior of surface-active compounds: 0-3 antifoaming agents, 4-6 W/O (water/oil) emulsifiers, 7-9 wetting agents, 8-18 O/W (oil/water) emulsifiers, 13-15 typical detergents and 10-18 solubilizers/hydrotropes. The HLB value can only be used as a preliminary guide, and further analysis by more exact and precise analytical techniques is required.…”
Section: Tensioactive Propertiesmentioning
confidence: 99%
See 3 more Smart Citations